2016
DOI: 10.1111/lam.12558
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Dekkera bruxellensis in a sugarcane-based fuel ethanol fermentation plant

Abstract: The presence of the yeast Dekkera bruxellensis is sometimes attributed to a decline in the industrial productivity of ethanol since it has a more limited fermentation capacity than Saccharomyces cerevisiae. Although its adaptability to the industrial environment has been noted, so far, there has been no evidence to determine the source of this contamination. In this study, we provide evidence to show that D. bruxellensis comes from the fields together with the harvested cane and is then accumulated and recircu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We have just reported that D. bruxellensis is introduced in the industrial process at the beginning of the harvest season with the sugarcane and first accumulated in the wash water that is further recirculated over the season (Da Silva et al 2016). Therefore, the heating of this wash water could prevent the input of D. bruxellensis cells from the fields and impede its accumulation in the recycled water.…”
Section: Resultsmentioning
confidence: 99%
“…We have just reported that D. bruxellensis is introduced in the industrial process at the beginning of the harvest season with the sugarcane and first accumulated in the wash water that is further recirculated over the season (Da Silva et al 2016). Therefore, the heating of this wash water could prevent the input of D. bruxellensis cells from the fields and impede its accumulation in the recycled water.…”
Section: Resultsmentioning
confidence: 99%
“…The strains of B. bruxellensis used in the present work were previously isolated from fuel ethanol production processes (Table 1) and identified by molecular biology tools (da Silva, Leite, & de Morais, 2016). Strains were maintained in yeast extract peptone dextrose (YPD) medium (10 g/L yeast extract, 20 g/L glucose, 20 g/L bacteriological peptone and 20 g/L agar) with constant transfers to new Petri dishes in order to keep cell colonies fresh (Leite et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, the suspensions were submitted to serial dilutions with 0.85% sterile NaCl 0.9% w/v solution and 100 mL of each dilution were plated on synthetic medium containing 1.7 g/L yeast nitrogen base (YNB) without amino acids and ammonium (Sigma-Aldrich, St. Luis, USA), 20 g/L glucose and 5 g/L ammonium sulphate, supplemented with antibiotics and cycloheximide as above. The plates were incubated for five days at 30 o C. The colonies were transferred for YPD plates (10 g/L yeast extract, 20 g/L peptone, 20 g/L glucose and 20 g/L bacto-agar) and incubated for more five days at 30 o C. Colonies were separated by morphological inspection and checked for purity [23][24][25].…”
Section: Soil Processing and Yeast Isolationmentioning
confidence: 99%